Penerapan Model Pembelajaran Team Assisted Individually Dalam Meningkatkan Kreativitas Belajar Siswa Pada Mata Pelajaran PAI - Mutmainnah, Mutmainnah; P, Sudirman; Mytra, Prima (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
The aim of implementing the Team Assisted Individually (TAI) model to enhance students' learning creativity in the subject of Islamic Religious Education (PAI) for class XI OTP 4. The study employed the classroom action research method with participants from class XI OTP 4. Two cycles were implemented, each consisting of planning, action, observation, and reflection. Data were collected through questionnaires, observations, tests, and documentation, with analysis using N-gain analysis. The results indicated a significant improvement. The pre-action questionnaire results showed 58.82% in the less category, while in Cycle I, it increased to 74.72% in the good category. Pre-action observation was 59.61% in the less category, improving to 78.84% in Cycle I, and reaching 88.46% in Cycle II in the very good category. The pre-action test result was 50.16% in the less category, increasing to 67.68% in Cycle I, and reaching 88.28% in Cycle II in the very good category. The increase in students' learning creativity, measured by an N-gain of 0.76%, indicated a high improvement. In conclusion, the TAI model is effective in significantly enhancing the learning creativity of PAI for class XI OTP 4 at SMKN 1 Sinjai.